ANALISIS RASIO KEUANGAN UNTUK MENILAI KINERJA KEUANGAN PADA PT ACSET INDONUSA TBK PERIODE TAHUN 2019-2023 - Zeze Zakaria Hamzah; Muchammad Hamdani; Ofi Khoirunnisa; Jarot Wuryanto (Institut Teknologi dan Bisnis Dewantara, 2026)
This study aims to assess the financial performance of PT. Acset Indonusa Tbk which is studied based on financial ratio analysis using liquidity ratio, solvency ratio, profitability ratio, and activity ratio of PT Acset Indonusa tbk for the period 2019-2023. The results of this study indicate that the Financial Performance of PT Acset Indonusa Tbk for the 2019-2023 Period based on the Liquidity Ratio (current ratio and quick ratio) can be concluded from the results of the study stated in good condition, Financial Performance of PT Acset Indonusa Tbk for the 2019-2023 Period based on the Solvency Ratio (debt to asset ratio and debt to equity ratio) can be concluded from the results of the study that the company is increasingly reducing its dependence on debt and relying more on equity or capital, Financial Performance of PT Acset Indonusa Tbk for the 2019-2023 Period based on the Profitability Ratio (net profit margin and return on equity) can be concluded from the results of the study stated in poor condition, Financial Performance of PT. Acset Indonusa Tbk for the 2019-2023 period based on the Activity Ratio (fixed asset turnover and total asset turnover) can be concluded from the research results that it is in good condition.